PENGARUH PEMBERIAN BEBERAPA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa Linnaeus) - I Gusti Ngurah Alit Wiswasta; Ni Putu Pandawani; I Made Suryana; Ni Putu Eka Pratiwi; Lorensius Joeng (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
Research entitled the effect of applying several types of manure on the growth and yield of salad plants (Lactuca sativa L) was carried out in experimental gardens Jalan Banteng Denpasar and the Agrotechnology Laboratory, Faculty of Agriculture and Business Mahasaraswati University Denpasar from February to May 2021. The research used a Randomized Group Design (RAK) with 5 treatments and repeated 5 times so that 25 experimental units were obtained. Treatment 5 consisted of 4 types of manure and 1 control namely: cow manure, chicken manure, goat manure, pig manure and control without fertilizer. The aim of this research is: To determine the growth and yield of lettuce plants given several different types of manure, namely cow, chicken, goat and pig manure. To find out which manure can provide the best growth and yield of lettuce plants, including cow, chicken, goat and pig manure. The results and conclusions of this research are: The application of several types of manure at harvest time resulted in an increase in the fresh weight of salad plants without roots, namely an increase of 266.90% respectively when giving cow manure;81.29% on giving chicken manure; 66.18% for goat manure and 22.30% for pig manure compared to salad plants without manure. Giving cow manure turned out to provide the best growth and yield of salad plants compared to giving chicken manure, goat manure or pig manure. To get better salad crop results, it is recommended to use cow manure rather than using chicken manure, goat manure or pig manure.